Pattern Signalling in Health Information Monitoring Systems - Levine, A.; Mandel, S. P. H.; Santamaria, A. (Methods of Information in Medicine, 1977)
Two examples of active health hazard monitoring systems are compared and contrasted, namely the World Health Organization’s Research Centre for International Monitoring of Adverse Reactions to Drugs which monitors side-effects of therapeutic drugs, and the »Programma de Investigaciön de Modelos de Prestaciön de Servicios de Salud« (PRIMOPS) which operates in Cali, Colombia, and monitors the activities, services and coverage of a community health system and its impact on the health of the community. These are just two examples of rapidly proliferating monitoring systems in which reports on adverse events are being submitted to a central clearing house by a network of reporting stations. It is shown how a Centre-Batch matrix constructed from the information contained in these reports can be analyzed to extract from it latent patterns. The detection of such patterns generates a warning signal, which in turn provides the incentive for further investigative action to be undertaken. These studies open up other areas of research, including the identification of the philosophical relationships between suspicion, evidence, statistical inference and action.
Keywords: Drug Monitoring; Adverse Events; Signals; Centre-Batch Matrix; Latent Patterns; Ordering Function